Cytopathological diagnoses obtained in endobronchial ultrasound-guided transbronchial needle aspiration – a single-center one-year analysis - Zając, Paweł; Kądziołka, Wojciech; Kaznowska, Ewa (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Endobronchial ultrasound-guided fine needle aspiration (EBUS-FNA) is a widely adopted technique that replaces mediastinoscopy for the diagnosis of mediastinal lesions, significantly improving patient safety. This study assesses its diagnostic effectiveness and compares procedural quality with the existing literature, in order to identify characteristics of the patient population referred to the center. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. During a year-long retrospective analysis, data from 312 EBUS-FNA procedures were collected, resulting in a final study group of 274 patients. For patients initially without a definitive diagnosis, reinterventions were conducted, typically with additional EBUS or tissue biopsy, followed by precise statistical analyses and calculations. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. The sensitivity of the EBUS examination to detect sarcoidosis, non-small cell lung cancer, small cell lung cancer, and lymphoproliferative disorders was determined to be 87.36%, 87.23%, 91.30% and 20%, respectively, based on false negative findings. Among patients who received a final diagnosis (n=237), a significant majority, i.e. 206 individuals or 86.92%, obtained it based on the first intervention. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. EBUS-TBNA is an effective method to diagnose the cause of mediastinal lymphadenopathy, allowing for a definitive diagnosis in a significant majority of patients in the first intervention and showing high sensitivity in detecting metastatic malignant lymph node involvement and sarcoidosis.